A tale of both sides of Iapetus – upper Darriwilian (Ordovician) graptolite faunal dynamics on the edges of two continents - Maletz, Jörg; Egenhoff, Sven; Böhme, Martina; Asch, Robert; Borowski, Katarina; Höntzsch, Stefan; Kirsch, Moritz; Werner, Mirko (Canadian Journal of Earth Sciences, 2011)
Ordovician graptolite faunal compositions between the Laurentia and Baltica margins of the Iapetus Ocean differ considerably in the upper Darriwilian (Da 3 – Da 4; upper Middle Ordovician). Detailed investigation of a number of sections in the Table Head and Goose Tickle groups in western Newfoundland and the Elnes Formation of Norway provides important new faunal data for the interval from the Holmograptus lentus Biozone to the Dicellograptus vagus Biozone. The Nicholsonograptus fasciculatus and Pterograptus elegans biozones are introduced for the Table Head and Goose Tickle groups and can be recognized widely in North America. The characteristic, but poorly correlatable, shallow-water endemic faunas of the platform regions (Atlantic and Pacific faunal realms) grade into the cosmopolitan oceanic graptolite faunas (isograptid biofacies) and provide a means to precisely correlate cold-water and warm-water endemic graptolite faunas through transitional zones. The faunal differences between western Newfoundland and Scandinavia are less pronounced than hitherto assumed, and many faunal elements can now be recognized in both regions, allowing for a more precise biostratigraphic correlation. The paleobiogeographic differentiation of both regions has been based on few, but usually extremely common faunal elements, masking the presence of important biostratigraphic marker species.